Spotted Substrates for Focal Presentation of Proteins to Cells. (November 2002) - Kummer, Terrance T.; Nishimune, Hiroshi; Wong, Rachel O.L.; Sanes, Joshua R.
Neurites and other cell processes encounter localized deposits of signaling factors as they grow. The difficulty in generating patterned artificial substrates has hindered the analysis of these instructive factors in vitro. Here we report a simple method for presenting cultured cells with small spots of protein on an otherwise uniform substrate. We use a biolistic device called a gene gun to deposit 0.1–5 μm fluorescent dots of pure protein on or beneath a growth-promoting substrate. Using this technique, we demonstrate local presynaptic differentiation of motoneurons in response to dots of a polycation. We also show that biotin-avidin and antibody-antigen interactions can be used to prepare spots from more dilute, more labile, or less abundant proteins. This method should prove useful for analyzing extracellular signaling molecules that act focally on neurons or other cell types.